Membrane-Fusing Vehicles for Re-Sensitizing Transporter-Mediated Multiple-Drug Resistance in Cancer - Sahel Vahdati; Alf Lamprecht (Pharmaceutics, 2024)
Reversing the multiple drug resistance (MDR) arising from the overexpression of the efflux transporters often fails mainly due to the high toxicity or the poor water solubility of the inhibitors of these transporters. Here, we demonstrate the delivery of an inhibitor targeting three ABC transporters (ABCB1, ABCC1 and ABCG2) directly to the cell membrane using membrane-fusing vehicles (MFVs). Three different transfected MDCK II cell lines, along with parental cells, were used to investigate the inhibitory effect of cyclosporine A (CsA) in solution versus direct delivery to the cell membrane. CsA-loaded MFVs successfully reversed MDR for all three investigated efflux transporters at significantly lower concentrations compared with CsA in solution. Results showed a 15-fold decrease in the IC50 value for ABCB1, a 7-fold decrease for ABCC1 and an 11-fold decrease for ABCG2. We observed binding site specificity for ABCB1 and ABCG2 transporters. Lower concentrations of empty MFVs along with CsA contribute to the inhibition of Hoechst 33342 efflux. However, higher concentrations of CsA along with the high amount of MFVs activated transport via the H-binding site. This supports the conclusion that MFVs can be useful beyond their role as delivery systems and also help to elucidate differences between these transporters and their binding sites.